2015
DOI: 10.1007/s11663-015-0397-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Mechanical Properties of Hydroxyapatite Bilayer Coatings Deposited on 316L SS by Sol–Gel Method

Abstract: The present paper reports on the influence of the addition of TiO 2 and SiO 2 oxides as sub-layer, on the morphological and mechanical properties of the hydroxyapatite (HAP) bioceramic coatings deposited on 316L stainless steel by sol-gel method in order to improve the properties of hydroxyapatite and expand its clinical application. The stability of the sols suspensions was evaluated by measuring the time dependence of the viscosity. Annealed properties of the coatings were analyzed by XPS, XRD, SEM, and EDS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the same way, TiO 2 sol was kept closely capped and aged for 24 h at the temperature of 100°C. The effect of temperature of TiO 2 aging sol on the film morphology has been discussed and detailed in [12].…”
Section: Materials and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same way, TiO 2 sol was kept closely capped and aged for 24 h at the temperature of 100°C. The effect of temperature of TiO 2 aging sol on the film morphology has been discussed and detailed in [12].…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…As a conclusion, we showed that the TiO 2 sub-layer significantly improves the hardness of the HAP coating. In [12] it is shown that the microhardness of the HAP coating, which is about of 459 HV (4.50 GPa) increases with the addition of the TiO 2 and SiO 2 inner layers, to reach approximately 530 HV (5.19 GPa) for the global HAP bilayer coatings. In addition, the hardness values obtained from both classic tests in microindentation and the continuous stiffness measurement mode in nanoindentation are slightly different.…”
Section: Hardness and Elastic Modulus Of The Uncoated And Hap Tio 2 mentioning
confidence: 99%
See 1 more Smart Citation
“…An extremely high temperature (6000-10,000°C) is applied in plasma-spray deposition can decompose the HAp properties into tricalcium phosphate, tetra-calcium phosphate, calcium oxide (CaO), and others amorphous phases [41,42]. When increasing annealing temperature from 375 to 500°C, the adhesion strength between HAp coating and the substrate increases [43,44].…”
Section: Sol-gel Dip-coating Methodsmentioning
confidence: 99%
“…Numerous studies [25][26][27][28][29] have investigated the variation of the microstructural, compositional, morphological, or surface properties of such coatings and their influence on the bioactivity, mechanical, and bonding strength. There is also another approach, consisting of the production of layered composite coatings, where the oxide layer, e.g., TiO 2 [30][31][32], ZrO 2 [32][33][34], Al 2 O 3 [26,31], and SiO 2 [30], is applied directly to the substrate and the HAp layer is deposited on top of it. This solution seems to have some advantages, e.g., better control over the composition and morphology of individual layers, as well as potentially much better isolation of the substrate in the event of dissolution of the HAp layer after implantation.…”
Section: Introductionmentioning
confidence: 99%